NMDAR Antibodies and New-Onset Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs, 2009)
The frequency and significance of antibodies to NMDAR were determined in 19 adolescents and young women, aged 15 to 45 years, with unexplained new-onset epilepsies, seen between Jan 2005 and June 2007 at the University of Bonn, Germany; Univ of Pennsylvania, Philadelphia; and John Radcliffe Hospital, Oxford, UK.